STANDARISASI PENATAAN GUEST SUPPLIES DALAM MENINGKATKAN JUMLAH TAMU PADA HOTEL BRONGTO DI YOGYAKARTA - Deanne Sisilia Yessika Rumengan; Yulianto Yulianto (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2014)
Hotel is one of the most important elements in the chain of much hotel tourism. Since it is still thrive  despite the management is still traditional. At the time city hotel is  a special hotel building as function business occupancy of room. Housekeeping classified into the back of the house because some of its service activities nota big deal directly with guests. Although there are some activities that allow officers to communication directly with the guests, for example, when preparing the guest room (make-up room) or about the arrangement of the guest room supplies complain in complete. Housekeeping should understand the mean or the words of guest room supplies it. Structuring is one important activity in preparing the guest room, where the supplies needed to prepare the employee must be attention to accuracy and neat also cleanliness in organize guest supplies in the hotel guest room.Where the supplies needed to prepare the employes must be attention to accuracy and neatness also clean lines in organize guest supplies in the hotel guest room. The problem in each hotel guest is structuring guest supplies not complite in guest room. This matter requires effort the management of Hotel Brongto in order to maximize the ability  of employee Hotel Brongto special in housekeeping to organize the guest supplies properly and correctly.